2006
DOI: 10.1007/s00264-006-0286-5
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric analyses of the cervical superior facets and implications for facet dislocation

Abstract: The articular facets of the cervical spine have been well addressed; however, little information is available on the relationship of the superior facets of the cervical spine to traumatic dislocation in the literature. Morphometric analyses of the superior facets of 30 dried cervical spines from C3 to C7 were performed to determine any morphological differences. The angle of the superior facet with respect to the transverse plane was also measured on computed tomography (CT) scans of 30 patients having neck in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 15 publications
1
18
0
Order By: Relevance
“…Transfacet fixation has infrequently been used for cervical column stabilization (Liu et al, 2008), even though it has been shown to carry a smaller risk of nerve root injury (Liu et al, 2006), which is why it should be considered as an alternative to transpedicular fixation (Liu et al, 2008;Jones et al, 1997). Ebraheim et al (2008) reported a decrease in vertical length from C3-C7 of the superior articular facets, with no significant difference by gender or side. On the other hand, we observed a progressive decrease from C3-C6.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…Transfacet fixation has infrequently been used for cervical column stabilization (Liu et al, 2008), even though it has been shown to carry a smaller risk of nerve root injury (Liu et al, 2006), which is why it should be considered as an alternative to transpedicular fixation (Liu et al, 2008;Jones et al, 1997). Ebraheim et al (2008) reported a decrease in vertical length from C3-C7 of the superior articular facets, with no significant difference by gender or side. On the other hand, we observed a progressive decrease from C3-C6.…”
Section: Discussionmentioning
confidence: 85%
“…It is thought that orientation and size of articular facets are related to the luxation of the articulation. This luxation is most commonly present at C5-C6 when unilateral and at C6-C7 when bilateral (Ebraheim et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although pure rotation without linear translation can occur at the proximal end of the chain in the atlanto-occipital joint, which acts as a hinge due to the depth of the atlantal sockets, 15 the presence of translations indicates movement of the cervical vertebrae. Small translations without rotation can occur between vertebrae, primarily at the distal end of the chain (C5-7), 16 but these are extremely small compared with the translation of the head relative to the torso when the cervical chain (C1-7) moves collectively in the sagittal plane (ie, cervical spine flexion-extension). We did not attempt to statistically analyze differences among the limited number of ATs, but the separated but parallel lines in the angular variables suggested small variations in atlanto-occipital manipulation by each AT (Figures 2A and 3A).…”
Section: Resultsmentioning
confidence: 99%